AB1097 Surgical interventions of the cervical and/or lumbar spine in patients with fibromyalgia. (23rd January 2014) - Figuls Poch, R.; Garcia-Diaz, S.; Corominas, H.; Reina, D.; Cerda, D.; Roig, D.; Gonzalez, M.; Paez, V.; Cordoba, A.; Vacas, M.; Casademont, M.
Abstract : Background: Patients with fibromyalgia can project their pain in the areas semiologically defined as targets of referred pain of spinal origin. A retrospective examination of clinical notes indicated that there was an excessive number of cervical and lumbar spine surgeries being carried out, and this prompted our study. Objectives: To specify the convenience of surgical intervention when there is a possibility that fibromyalgia pain may be confused with spinal pain. To detect previous spine surgery and the cause of its indication. Methods: The study was a retrospective design. We reviewed the medical records of the first 135 patients treated in our unit (from the period of 31/05/2010 until 31/12/2010) who were already diagnosed with fibromyalgia, and attended our clinic with the expectation of multidisciplinary treatment. Simultaneously, we reviewed the surgical decision criteria for root syndromes, degenerative discopathy and spondylolysis with spondylolisthesis. Results: We found that 11 patients (8%; 9 women, 2 men) out of 135, underwent cervical and/or lumbar spine surgery. Of those, there were 4 cases of cervical fusion (2 patients had one herniated disc and 2 other patients had two herniated discs); 5 cases of lumbar fusion (2 cases had with lysis of L5, 1 case herniated disc and the other 2 had no diagnosis); and 4 cases of laminectomy (all of them had herniated disc). Two patients were operated on more than one occasion: one, with both lumbar and cervical fusion; and the other, with a laminectomy and lumbar fusion. According to the literature reviewed, the criteria for surgical intervention of radiculopathy due to both cervical and lumbar discal herniation was: 1. Clinical criteria: a) untreated pain, multiple recurrences, b) persistent or progressive motor deficit; 2. Imaging: the presence of discal herniation with signs of nerve root involvement, in accordance with the clinical topography of the pain and neurological deficits; 3. Electromyography (EMG): active denervation signs in accordance with the clinical topography of pain and neuroimaging findings. Moreover, the criteria for surgery in lysis with listhesis was: severe pain that does not improve with conservative treatment, neurological changes, severe listhesis (grades III-IV) and progression of spondylolisthesis (in two consecutive radiological controls). There is no consensus on criteria for surgical indication in the nonspecific disc disease (without warning signs, without radiculopathy and non-inflammatory disease). Most of the articles reviewed showed that this surgery has similar results to the conservative treatment and with a much lower risk. Conclusions: In those patients where surgery is considered as an alternative, it would be prudent to consider the possibility of the existence of fibromyalgia. In those patients diagnosed with fibromyalgia, it is necessary to pay particular attention to meeting the decision criteria for surgical treatment and considering that the result of the surgery in a psychosomatic patient can be unpredictable. There should be consistency between the neuroimaging studies, clinical pain topography and semiology. Also, in cases of radicular syndrome, those have to be in accordance with neurophysiological studies. Disclosure of Interest: None Declared